2005
DOI: 10.1093/jxb/eri165
|View full text |Cite
|
Sign up to set email alerts
|

Pathogen-induced expression of a cecropin A-melittin antimicrobial peptide gene confers antifungal resistance in transgenic tobacco

Abstract: Expression of defensive genes from a promoter that is specifically activated in response to pathogen invasion is highly desirable for engineering disease-resistant plants. A plant transformation vector was constructed with transcriptional fusion between the pathogenresponsive win3.12T promoter from poplar and the gene encoding the novel cecropin A-melittin hybrid peptide (CEMA) with strong antimicrobial activity. This promoter-transgene combination was evaluated in transgenic tobacco (Nicotiana tabacum L. cv. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
61
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(68 citation statements)
references
References 41 publications
6
61
0
1
Order By: Relevance
“…F. oxysporum conidial suspension was mixed 1 : 9 with the protein extract, plated and incubated at RT in low light. Antifungal activity was determined as the number of germinated conidia CFU cm −2 (colony forming unit) after 48 h and 72 h post incubation (hpi) (Ntui et al 2011;Yevtushenko et al 2005). The experiment was set up as randomized complete block design with 3 replications, data collected were subjected to analysis of variance and graphed using Sigma Plot program.…”
Section: Antifungal Activity Against Fusarium Oxysporummentioning
confidence: 99%
“…F. oxysporum conidial suspension was mixed 1 : 9 with the protein extract, plated and incubated at RT in low light. Antifungal activity was determined as the number of germinated conidia CFU cm −2 (colony forming unit) after 48 h and 72 h post incubation (hpi) (Ntui et al 2011;Yevtushenko et al 2005). The experiment was set up as randomized complete block design with 3 replications, data collected were subjected to analysis of variance and graphed using Sigma Plot program.…”
Section: Antifungal Activity Against Fusarium Oxysporummentioning
confidence: 99%
“…Though it has been reported that the degree of antimicrobial activity is not dependent on the AMP production level in transgenic plants, 106 most of the publications furnish clear evidence for peptides' doseeffect activity. 82,100,107,108 Some investigators emphasize the possibility of synergism among different AMPs. [109][110][111] In vivo data for different antibacterial peptides show that defensins and linear peptides work in-synergy, 112,113 as exemplified by synergism between LL-37 and human b-defensin HBD-2.…”
Section: Prospective For Future Endeavorsmentioning
confidence: 99%
“…General propensity toward reducing fitness costs 117 as well as downgrading the co-evolutionary collapse of resistance to microbes has weighted the generation of plants expressing AMPs on-demand, by exploiting synthetic or native inducible promoters activated upon pathogen attack. 2,11,107,118,119 Employment of wounding and/or pathogeninducible promoters ensures high expression level of the peptide upon mechanical wounding and/or microbial infections. This may assist to avoid the development of pathogenic microbes capable of circumventing induced disease resistance, by e.g., mutation and/or synthesis of proteolytic agents.…”
Section: Prospective For Future Endeavorsmentioning
confidence: 99%
“…Transgenic model and crop plants expressing antimicrobial peptides (e.g., insect cecropins) have been shown to display resistance against various bacterial and fungal pathogens (9). Given that the level of protection by a single antimicrobial peptide is only moderate at best, efforts have been made to fuse two antimicrobial peptides (e.g., cecropin and melittin) to improve their efficacy in disease protection (10). Moreover, because antimicrobial peptides are inherently unstable due to their susceptibility to plant proteases, amino acids have been altered to improve their stability in plant tissues (11).…”
mentioning
confidence: 99%